1989
DOI: 10.1021/bi00451a047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monoclonal antibody binding on .alpha.-.beta..gamma. subunit interactions in the rod outer segment G protein, Gt

Abstract: The guanyl nucleotide binding regulatory protein of retinal rod outer segments, called Gt, that couples the photon receptor rhodopsin with the light-activated cGMP phosphodiesterase, can be resolved into two functional components, alpha t and beta gamma t. The effect of monoclonal antibody binding to the alpha t subunit of Gt on subunit association has been investigated in the present study. It was previously shown that this monoclonal antibody, mAb 4A, blocks interactions with rhodopsin and its epitope was lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Although a second surface of the ␣ subunit forms an even larger area of interaction with ␤␥ (33, 34), our studies concentrated on the N-terminal region for two important reasons. First, previous work by others showed that disruption of this region by deletion (36,37), proteolysis (38), or antibody binding (39,40) is sufficient to prevent ␣ from interacting with ␤␥. Second, mutations in the N-terminal region are unlikely to disrupt the overall three-dimensional structure of the ␣ subunit.…”
Section: Mutation Of a Conserved ␤␥ Contact Region In ␣ S And ␣ Q -mentioning
confidence: 99%
“…Although a second surface of the ␣ subunit forms an even larger area of interaction with ␤␥ (33, 34), our studies concentrated on the N-terminal region for two important reasons. First, previous work by others showed that disruption of this region by deletion (36,37), proteolysis (38), or antibody binding (39,40) is sufficient to prevent ␣ from interacting with ␤␥. Second, mutations in the N-terminal region are unlikely to disrupt the overall three-dimensional structure of the ␣ subunit.…”
Section: Mutation Of a Conserved ␤␥ Contact Region In ␣ S And ␣ Q -mentioning
confidence: 99%
“…Numerous biochemical (29,31,47,48) and mutational (49,50) studies have implicated the amino terminus of G protein ␣ subunits in the interaction with ␤␥ subunits. The resolution of the crystal structure of heterotrimeric G t (14) has confirmed that the amino-terminal helix of the ␣ t subunit is involved in forming a binding site for the ␤ t subunit.…”
Section: Fig 3 Identification Of ␣ T Proteolytic Fragments By Immunmentioning
confidence: 99%
“…As B binds independently to P 1 and P 2 , the binding constants (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) can be obtained: …”
Section: :1 and 2:1 Competitive Binding Stoichiometrymentioning
confidence: 99%
“…(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) shows that Eq. (3-17) is consistent with the definition of binding constant of B and P 1 , as shown in the Eq.…”
Section: :1 and 2:1 Competitive Binding Stoichiometrymentioning
confidence: 99%
See 1 more Smart Citation